Law as Minor Jurisprudence: Is it a Mistake? - Genevieve Renard Painter (Law Text Culture, 2017)
What is law as minor jurisprudence? Existing scholarship around the concept of minor jurisprudence associates it with processes that start something, found something, or stand outside something and, further, with processes that conceal or erase. To seek to clarify the meaning and effect of the phrase ‘“law as” … minor jurisprudence’, I consider cases of mistake that, as legal speech acts, transform a state of affairs. In Part I, I use JL Austin’s theory about speech acts to analyse how speech can be mistaken and how such mistakes may transform states of affairs, using cases of encounters between Indigenous, settler, and international legal orders. In Part II, I survey the debut of the Trump administration as a possible site of minor jurisprudence. Informed by this study of mistakes that help make minor jurisprudence, my investigation suggests that: 1) minor jurisprudence requires major jurisprudence to be cognizable; 2) little intrinsic to the concept of minor jurisprudence offers normative guidance; and 3) the idea of law as minor jurisprudence may be a mistake. If ‘law as’ is understood as a practice of legal knowledge, what matters is the process of drawing the line between major and minor, not the minor itself.